(untitled)
In this paper, we propose the concept of (, (φ^, q_φ ))-bipolar fuzzy ideals in BCK/BCI-algebras. We show that an (, q_φ )-bipolar fuzzy ideal is an (, (φ^, q_φ ))-bipolar fuzzy ideal. For a BCK/BCI-algebra, it has been shown that an (, (φ^, q_φ )-bipolar fuzzy ideal is an (, q)-bipolar fuzzy ideal of , but not conversely, and then an example is given. We introduce the concept of (, (φ^, q_φ ))-bipolar fuzzy fantastic ideals in BCK/BCI-algebras. It has been shown that an (, (φ^, q_φ ))-bipolar fuzzy fantastic ideal is an (, )-bipolar fuzzy ideal in BCK/BCI-algebras. Furthermore, the connection between (, (φ^, q_φ ))-bipolar fuzzy fantastic ideals and fantastic ideals are established. , number=4, journal=European Journal of Pure and Applied Mathematics, year=2024, month=Oct., pages=3973–3983